Is agent-neutral deontology possible? - HAMMERTON, Matthew (Institutional Knowledge at Singapore Management University, 2017)
It is commonly held that all deontological moral theories are agent-relative in the sense that they give each agent a special concern that she does not perform acts of a certain type rather than a general concern with the actions of all agents. Recently, Tom Dougherty has challenged this orthodoxy by arguing that agent-neutral deontology is possible. In this article I counter Dougherty's arguments and show that agent-neutral deontology is not possible.